2021
DOI: 10.1111/soru.12355
|View full text |Cite
|
Sign up to set email alerts
|

Going against the grain: Unravelling the habitus of older farmers to help facilitate generational renewal in agriculture

Abstract: Limited uptake of financial incentives, designed to confront global trends of an ageing farming population and low levels of land mobility, reveal resistance or at best ambivalence, amongst farmers towards altering existing farm management and ownership structures in later life. To uncover facets governing the mindset, disposition and practices of older farmers towards succession and retirement, this study draws on Bourdieu's notion of habitus. A multi-method triangulation methodology is employed to obtain in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…88, No. 2, June 2023 to describe the colorful context of the phenomena, and to benefit from the advantages of both qualitative and quantitative approaches (Conway et al 2021;Johnson, Onwuegbuzie, and Turner 2007;Small 2011). We found that gardening and subsistence farming are important and widespread across society, although it is declining.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…88, No. 2, June 2023 to describe the colorful context of the phenomena, and to benefit from the advantages of both qualitative and quantitative approaches (Conway et al 2021;Johnson, Onwuegbuzie, and Turner 2007;Small 2011). We found that gardening and subsistence farming are important and widespread across society, although it is declining.…”
Section: Introductionmentioning
confidence: 90%
“…Our data enable us to analyze the motivations of individuals and the factors influencing them to engage in subsistence farming. We used a mixed method approach to reveal the role of these factors and to be able to describe the colorful context of the phenomena, and to benefit from the advantages of both qualitative and quantitative approaches (Conway et al 2021; Johnson, Onwuegbuzie, and Turner 2007; Small 2011). We found that gardening and subsistence farming are important and widespread across society, although it is declining.…”
Section: Introductionmentioning
confidence: 99%
“…Chiswell [12] analysed the transfer of managerial control of family farms, and she emphasises the role of individualisation processes in intergenerational transfer. Many scholars [13][14][15] confirm that rural regeneration and especially intergenerational transfer in family farming is crucial to the continuity and future of family farms and also of rural society. Studies prove that the younger generation seeks and demands greater independence and autonomy, and if this is not possible, the succession can fail.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies prove that the younger generation seeks and demands greater independence and autonomy, and if this is not possible, the succession can fail. Conway et al [13] highlight that understanding the new farming habitus is crucial in order to appreciate all aspects of succession in farming communities. Habitus is also emphasised in the context of organic farming.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation